PERUBAHAN PENGGUNAAN LAHAN SAWAH MENJADI NON SAWAH DAN PENGARUHNYA TERHADAP KEBERLANJUTAN SAWAH LESTARI DI KABUPATEN KLATEN - Nugroho, Adi Setyo; Aji, Ananto; Indrayati, Ariyani (Geo-Image, 2017)
Land use changes are becoming increasingly uncontrollable, including wake up land coming from paddy fields and raising issues that affect all aspects of social, economic and cultural aspects. This study aims to determine the area of paddy land that converted to non-wetland land and its impact on rice production in Klaten Regency. The selected research object is based on the subdistrict kecamatan experiencing the widest change of land use and having rice production in Klaten Regency. Sub-districts selected by purposive sampling with data collection techniques that is observation, interviews, and documentation. The results of this study change the use of rice fields into non-rice fields during 2004 - 2014, namely (1) District Ceper area of 52.05 Ha, (2) District Delanggu 38.00 Ha, (3) North Katen District 125.00 Ha. There are some land use changes that are inconsistent with the spatial plants. Changes in the use of rice fields to nonsawah have a positive impact on the economy of the people and the negative impacts on rice productivity, the harvest from 2004 to 2014 several times decreased. The suggestion is that the government is serious about disseminating spatial plants to the community so that there will be no change of paddy field to non-rice field.